AKAD JUAL BELI DALAM TRADISI PASAR TERAPUNG MASYARAKAT BANJAR - HM Hanafiah (IAIN Ponorogo, 2015)
Abstract: Traditional trade of Banjar people in the floating market is unique since it is done in the market which is located in the middle of the river. In the transaction at the floating market, sellers and buyers still do sale and purchase agreement in accordance with the provisions of Islamic laws. In fact, the situation and condition at that time did not allow them to make transaction like sale and purchase as usual because the waves of the river could shake their canoes endangering their lives. According to scholars of syafi'iyah, the sale and purchase contract is not valid except with shigat which was pronounced